UNJUK KERJA MOTOR INDUKSI ROTOR LILIT SEBAGAI VARIABEL-TRANSFORMATOR - Subekti, Lukman (Jurusan Teknik Informatika Fakultas Teknologi Industri UPN "Veteran" Jogjakarta, 2009)
Generally induction motor is used as a tool to change electric power to mechanic one. In forced condition wound-rotor induction motor can be used as transformer. This case can be accepted for both machines work by induction principle. Stator is the primary side of a three phase-transformer. Magnetic field produced by stator cuts across rotor conduction. This induction voltage cases the rotor current to flow. However, induction motor is one of non-linear load and be able to cause harmonic in alternating current. The objective of this research is to acknowledge the work of wound-rotor induction motor when its function is changed into a transformer. The research was done by the wound rotor supplied sinusoidal voltage as the primary of a three phase transformer. The magnetic filed produced by rotor cuts across stator conductor. Rotor position was regulated from 0 degree,45 degree, 90 degree, 135, up to 360 degree. In stator winding, the amount of emf induced proportional to the rate of flux change and the number of its wound. The result of research shows that wound-rotor induction motor can be used as variable transformer. Voltage change obtained is about 8%. Voltage waved) form isdefect sinusoidal. The average value of Total Harmonic Distortion (THD) is 1.8% for displacement of rotor angle from 0 degree up to 360 degree